Development and Validation of a HPLC based analytical method, towards the determination of sugar concentration in processed black tea - Editor-in-chief, Technium (Technium BioChemMed, 2021)
A rapid and sensitive reversed phase High Performance Liquid Chromatographic (HPLC) method was developed and validated for the quantitative estimation of soluble sugars viz fructose, glucose and sucrose in black tea brew. The method includes an isocratic elution of mobile phase comprising 83% aqueous acetonitrile for 30 minutes at a flow rate of 1.5 mL/min over Zorbax NH2 (150 x 4.6 mm, 5µm) column at column oven temperature of 33 ºC. The detection was done using Reflective Index Detector (RID) at the temperature of 33 ºC. Validation was conducted with respect to selectivity, linearity and linear range, sensitivity, accuracy and precision. The calibration plots were linear in response with correlation coefficient (r2 ) value of 0.99 over the concentration range of 50 ppm – 1000 ppm for all three standard solutions. More than 98% recovery was observed during the recovery study of sugar spiked samples. The precision of the developed method in terms of Co-efficient of Variance (CV %) were in the range of 1.07-1.98, 0.85-1.15 and 0.9-1.92 at the spike levels of 0.25%, 0.375% and 0.5% respectively. Therefore, the methodology was found to be accurate, reproducible and sensitive, which could be successfully applied for the determination of sugar compounds in black tea brew.